Flexible work time in Germany: Do workers like it and how have employers exploited it over the cycle? - Jennifer Hunt (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
After describing qualitatively the increasingly flexible organization of work hours in Germany, I turn to the German Socio-Economic Panel to quantify practices and trends, and assess their effects on workers and employers. Measuring flexibility as the extent to which overtime is compensated with time off, and hence receives no overtime premium, I show that hourlypaid workers have undergone a regime shift towards more flexibility since 1984, while salaried workers have maintained an already high level of flexibility. I find weak evidence that flexibility causes workers to be slightly less satisfied with their work and more satisfied with their leisure. Over the boom and bust cycle of 2004-2009, I find that for hourly-paid workers in manufacturing, paid and unpaid overtime hours were equally cyclical, but that the cycle for unpaid overtime led the cycle for paid overtime. The results suggest that while the new practices do free employers to make more cyclical adjustments in hours, they have not eliminated the need for adjustments in paid overtime. I identify as constraints ceilings on cumulated overtime hours to be compensated with time off and the window within which the compensation in time off must occur.
Keywords: 330; Arbeitszeitgestaltung; Arbeitszufriedenheit; Konjunktur; Schätzung; Deutschland